The Need To Update The Dental Healthcare Community On Hand, Foot, And Mouth Disease - Zakaria NR; Abdul Aziz AH; Baharom N; Mohamed NA (Malaysian Dental Association, 2024)
Malaysian Dental Journal, Volume 45 Issue 2 Page (15–22)